Finite element modelling and field validation of prestressed concrete sleepers and fastening systems. Issue 5 (3rd May 2016) - Chen, Zhe; Andrawes, Bassem; Edwards, J. Riley
Abstract : Prestressed concrete sleepers and elastic fastening systems have been widely applied in North America to accommodate increased freight axle loading and the development of high-speed passenger rail systems. However, the design standard of the American Railway Engineering and Maintenance-of-Way Association remains unclear about the relationship between some critical design parameters and the vertical and lateral load paths through the track structure. In this study, field experimentation is conducted at the Transportation Technology Center in Pueblo, CO, and the test data are compared with finite element (FE) models of the track structure for model validation. Strain gauges and potentiometers are installed in the field to measure the response of concrete sleepers and fastening systems. The FE models consist of two parts: a detailed single-sleeper model to capture the local response of the loaded rail seat, and a global multi-sleeper model to provide realistic boundary conditions for the detailed model. The bond–slip behaviour between concrete and prestressing wires, and inelastic material properties are incorporated in the FE models. Good agreement is observed between the test measurement and the model output. The validated FE model is used for parametric studies on the some critical design parameters, and conclusions about the load path through the sleepers and fastening systems are summarised.